2020
DOI: 10.3390/cancers12102873
|View full text |Cite
|
Sign up to set email alerts
|

Association of Common Variants of TNFSF13 and TNFRSF13B Genes with CLL Risk and Clinical Picture, as Well as Expression of Their Products—APRIL and TACI Molecules

Abstract: Interactions between APRIL (TNFSF13) and its receptor TACI (TNFRSF13B) are implicated in providing survival benefits for chronic lymphocytic leukaemia (CLL) cells. Here we explored the relationship between TNFSF13 and TNFRSF13B SNPs and expression of APRIL and TACI molecules and performed extended case-control study to evaluate earlier observations. Expression of APRIL and TACI was detected by FACS for 72 and 145 patients, respectively, and soluble APRIL was measured by ELISA in plasma of 122 patients. Genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(122 reference statements)
1
8
0
Order By: Relevance
“…A combined analysis of African and European ancestry populations identified a missense variant (rs34562254) in TNFRSF13B associated with multiple myeloma risk [50]. It has also been reported that several genetic variants in TNFRSF13B influence gene expression and susceptibility to chronic lymphocytic leukaemia [51]. Furthermore, a significant association of TNFRSF13B rs7501462 with survival was identified in a large cohort of 10,084 patients with invasive epithelial ovarian cancer [52].…”
Section: Discussionmentioning
confidence: 97%
“…A combined analysis of African and European ancestry populations identified a missense variant (rs34562254) in TNFRSF13B associated with multiple myeloma risk [50]. It has also been reported that several genetic variants in TNFRSF13B influence gene expression and susceptibility to chronic lymphocytic leukaemia [51]. Furthermore, a significant association of TNFRSF13B rs7501462 with survival was identified in a large cohort of 10,084 patients with invasive epithelial ovarian cancer [52].…”
Section: Discussionmentioning
confidence: 97%
“…11 The higher stability of the ligand-receptor complex could physiologically produce a proliferative stimulus, favoring leukemogenesis, similarly to the phenomenon observed in the case of overexpression of TNFSF13, which may cause a higher susceptibility to CLL due to the saturation (in terms of a more significant number of interactions) of TNFRSF13B. 4 Larger data support our observations; in fact, in a recent nationwide study on cancer-prone syndromes, TNFRSF13B was reported among relevant genes associated with the childhood onset of glioma, Burkitt lymphoma and Langerhans cell histiocytosis. 3 Furthermore, as stated above, common TNFRSF13B variants and TACI expression were recently correlated with the risk of CLL onset.…”
Section: Introductionmentioning
confidence: 92%
“…3 Furthermore, common variants of TNFRSF13B and TNFSF13 (encoding APRIL, the main TACI-ligand) were recently associated with the chronic lymphocytic leukemia (CLL) risk, as well as the expression of their products (TACI and APRIL). 4 Nonetheless, the involvement of constitutive TNFRSF13B alterations in acute myeloid leukemia (AML) remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…13 In this sense, numerous studies have demonstrated the role of specific genes in the development of different types of cancer. [14][15][16][17][18][19] The genetic atlas of cancer is a priority for cell and molecular biology with a view to discovering the different signaling pathways involved, and identifying new targets for the development of antitumor diagnostics and drugs.…”
Section: Cancer Incidence: Factors Involved In Its Origin and Develop...mentioning
confidence: 99%